Geneza i koncepcja tzw. polityki dochodów w zachodniej Europie - Rose, Edward (Wydział Prawa i Administracji UAM, 1967)
One of the features characterising the evolution of contemporary capitalism is the fundamental change of policy of certain countries in the shaping of their economic life. In the majority of capitalist countries, especially in the west, the share of the state in the national income has grown immeasurably in comparison to its pre-war size. This was created by the greater possibilities of direct influence of these states on realizing the postulates of economic growth and full employment. The rise of national economy — totaly or calculated per head- is compatible with the increase in the general purchasing capacity of the population. A greater demand for articles of consumption gives rise to pressure on prices, and where there is a lack of balance between supply and demand it is rectified by import. A fall in the purchasing power of domestic currency in the home market and its danger from trade balance, creates the threat of -inflation. Prevention of inflation becomes a struggle to keep the balance of prices. Some governments when faced with inflation are to obliged to find means of controlling it, and resort to direct as well as indirect action (be resticting or arresting its upsurge, which influences the increase of purchasing capacity of the population). Direct action does not arrest the upsurge as such, but confines is rate to such norms, so that the accompanying phenomenon does not lead to a rapid rise in purchasing power of the population. Some countries consider that the way to attain this goal is not by order of authority but by direct agreement between the parties concerned- e.g. 'the producers and workers as regards wages, or between producers and the authorities as to prices. After World War II there was inaugarated in Holland a simultaneous control on the movement of wages and prices. This concept known as income policy, is in actual practice in Great Britain and France. Both countries, though with some difficulties, maintain this policy along centrally established planned directives, and do not treat it as a temporary means to prevent the threat of inflation, but as a long term policy which would show its real value after a longer period. The income policy in the countries concerned is not very popular and is strongly opposed by the Trade Unions. Irrespective of the results gained from attempts to realize the income policy, the concept of regular and planned control of income distribution by the State constitutes a contribution to the changes in patterns of thinking which take place in capitalist countries.
Genesis and concept of so-called income policy in Western Europe